2010
DOI: 10.1152/jn.00437.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of the Critical Cochlea: Hopf—a Bifurcation—Is Better Than None

Abstract: Hudspeth AJ, Jülicher F, Martin P. A critique of the critical cochlea: Hopf-a bifurcation-is better than none. J Neurophysiol 104: 1219-1229. First published June 10, 2010 doi:10.1152/jn.00437.2010. The sense of hearing achieves its striking sensitivity, frequency selectivity, and dynamic range through an active process mediated by the inner ear's mechanoreceptive hair cells. Although the active process renders hearing highly nonlinear and produces a wealth of complex behaviors, these various characteristics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 93 publications
4
126
2
Order By: Relevance
“…In mammals, manifestations of the so-called cochlear amplifier are the high sensitivity and frequency selectivity with respect to weak stimuli, the compressive nonlinearity, and the generation of oto-acoustic emissions. All aspects of the active process are consistent with the notion of nonlinear oscillators at work in the cochlea [2]. This regards in particular the properties of the active wave traveling in the cochlea, which could be generically described in terms of critical oscillators and has been explored previously in the frequency (Fourier) domain [1].…”
supporting
confidence: 79%
“…In mammals, manifestations of the so-called cochlear amplifier are the high sensitivity and frequency selectivity with respect to weak stimuli, the compressive nonlinearity, and the generation of oto-acoustic emissions. All aspects of the active process are consistent with the notion of nonlinear oscillators at work in the cochlea [2]. This regards in particular the properties of the active wave traveling in the cochlea, which could be generically described in terms of critical oscillators and has been explored previously in the frequency (Fourier) domain [1].…”
supporting
confidence: 79%
“…33 In particular, recent works have shown that the "phase response curve," a metric of the dynamics of a neuronal oscillator perturbed by weak noise, is directly related to its linear transfer function, 25,69 so that a direct link can be made between dynamics and information encoding into neuronal spike timing. 69 Physiological studies on several species have shown and discussed essential nonlinearities of sensory encoding in auditory, 22,38 visual, 40,56,59 vestibular, 66 mechanosensory, 61 and electrosensory 14,16 systems. In many cases, nonlinearities were associated with non-weak stimuli or with the existence of bursting patterns of neural firing.…”
Section: Introductionmentioning
confidence: 99%
“…Please cite this article in press as: Albert and Kozlov, Comparative Aspects of Hearing in Vertebrates and Insects with Antennal Ears, Current Biology (2016), http://dx.doi.org/10.1016/j.cub.2016 to maintain the system's control parameters in the desired range in order to benefit functionally from the oscillatory instability) [12]. Thus, natural selection has produced ears that operate close to a bifurcation [12], which produces amplification, frequency selectivity, and a gain control -characteristics that underlie sensitive hearing in vertebrates as well as in some insects.…”
Section: Curbio 13179mentioning
confidence: 99%